2019
DOI: 10.1111/jerd.12457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preparation designs on marginal adaptation and failure load of full‐coverage occlusal veneers after thermomechanical aging simulation

Abstract: Objectives To evaluate the fracture resistance and marginal quality of maxillary molars restored using lithium disilicate glass‐ceramic (LDG) occlusal veneers with two preparation designs. Methods Sixteen extracted maxillary molars were assigned to two groups (n = 8). In group 1 (G1), the teeth received a preparation for a conservative full‐coverage occlusal veneer restoration with a 90° rounded shoulder margin. In group 2 (G2), the teeth underwent a 1‐mm cusp reduction with a marginal chamfer. LDG restoration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
2
36
0
3
Order By: Relevance
“…(46) The circumferential fullcoverage preparation design chosen in this study was in agreement with the preparation guidelines for minimally invasive restorations shown in previous studies. (13,15,47) All the teeth were prepared using milling machine to ensure proper standardization for all the prepared teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(46) The circumferential fullcoverage preparation design chosen in this study was in agreement with the preparation guidelines for minimally invasive restorations shown in previous studies. (13,15,47) All the teeth were prepared using milling machine to ensure proper standardization for all the prepared teeth.…”
Section: Discussionmentioning
confidence: 99%
“…(2,6,9,10,11) Occlusal veneers consist of thin overlay coverage with non-retentive form. (13) The availability of ceramic materials that could be constructed in thin sections and still have high mechanical properties accompanied with improved bonding capabilities make the occlusal veneers a reliable successful prosthetic treatment option. Lithium disilicate glass ceramic is considered the strongest ceramic material that could meet these Results: The results of this study revealed that e.max processed by conventional wax technique recorded the highest vertical marginal gap mean values followed by Celtra processed by conventional wax technique then Celtra processed by CAD wax technique while e.max processed by CAD wax technique recorded the lowest mean values.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafine occlusal veneers represent a conservative alternative to traditional techniques, they also allow only a strategic reduction of healthy dental structure or perhaps no preparation, dentists should ideally choose flat and circumferential designs to improve clinical performance and longevity, although other designs of preparations such as: occlusal veneers with circumferential shoulder line or occlusal veneers with intracoronal extension are also described [9][10] . However, studies in 2018 recommend designs of preparations such as those applied in this report, since these forms of preparation allow the dental technician to manufacture a well-adjusted and uniform thickness restoration and thus obtain a very low fracture and disunity rate 1,11 .…”
Section: Odontología Odontologíamentioning
confidence: 99%
“…Las carillas oclusales ultrafinas representan una alternativa conservadora a las técnicas tradicionales, además permiten solo una reducción estratégica de la estructura dental sana o quizá ninguna preparación, los odontólogos deberían elegir de manera ideal, diseños planos y circunferenciales para mejorar el rendimiento clínico y longevidad, aunque también se describen otros diseños de preparaciones como: carillas oclusales con línea de hombro circunferencial o carillas oclusales con extensión intracoronal [9][10] ; sin embargo, estudios en el 2018 recomiendan diseños de preparaciones como las aplicadas en este reporte, puesto que estas formas de preparación le permiten al técnico dental, fabricar una restauración bien ajustada y de espesor uniforme y así obtener una tasa de fractura y desunión muy baja 1,11 .…”
Section: Odontología Odontologíaunclassified
See 1 more Smart Citation